Using The Refugia Plant as an Alternative Habitat for Predatory Insects On Potato Plants - M. Sarjan; Hery Haryanto; Bambang Supeno; Amrul Jihadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
One of the technological innovations that is very relevant for the implementation of IPM is habitat manipulation using refugia plants to conserve predatory insect. The aim of this study was to determine the effect of different species of Refugia plants on the diversity and species richness of predator on potato plants and their production yields. The research method used was a field experimental method with a randomized block design with 5 treatments of Refugia plant species repeated 3 times. The data were analyzed using analysis of variance (ANOVA) and are further tested by Honest Significant Difference (BNJ) analysis at a significance level of 5 percent. The results showed that nine predatory species were found in refugia and potato plants, namely Crytoleamus montrouzieri, Cocinella transversalis, Coleophora inaequalis, Monocielus sexmaculatus, Axion plagiatum, Coleophora reniplagiata, Illeis koebelei, Mantidae and Formicidae. The insect diversity index (H') of the predators found was rated as moderate for all treatments, ranging from 1.2 to 1.9.